Peranan Bimbingan Konseling Islam dalam Menumbuhkan Kecerdasan Spiritual Siswa - Saparwadi Saparwadi; Mohamad Syafiq (Muthmainnah: Jurnal Bimbingan Konseling Islam dan Psikosufistik, 2025)
This study examines the implementation of Islamic Counseling Guidance (Bimbingan Konseling Islam/BKI) in fostering the spiritual quotient (SQ) of students at Madrasah Aliyah Darullughah Wadda’wah Pasuruan. Motivated by the imbalance in modern education, which tends to be materialistic and neglects the esoteric aspect, this research employs a qualitative approach with a case study design to explore the role of BKI as an intervention strategy. Data were collected through interviews, observations, and documentation, and then analyzed using the interactive model of Miles and Huberman. The findings reveal that the implementation of BKI was carried out in a holistic and systematic manner through the stages of planning, implementation (via techniques such as Qur'anic Cognitive Restructuring, halaqah [study circles], and spiritual retreats), monitoring (using a Spiritual Diary), and evaluation. As a result, this approach successfully created a supportive spiritual ecology that fostered the internalization of spiritual values such as tawakkal (reliance on God) and sabar (patience), and built religious-based mental resilience (religious coping) in students. This study concludes that BKI is effective not only in resolving behavioral issues but also in shaping self-meaning, transcendental awareness, and inner balance, thereby establishing spiritual intelligence as a foundation for students' academic and social success.